The marketing board system : proceedings of an international conference - Onitiri, H. M. A.; Olatunbosun, Dupe.; Nigerian Institute of Social and Economic Research ([Ibadan] : Nigerian Institute of Social and Economic Research, 1974)
The papers presented in this volume were presented at a conference organized with the aim of bringing together economists interested in the subject of marketing boards and officials who have been closely concerned with the practical problems of operating marketing boards and similar situations.
Includes bibliographical references.
rpm 22/01/2019
Loans
Keywords: Marketing boards